PENDAMPINGAN ANALISIS KRITIS FENOMENA CHILDFREE MELALUI TAFSIR MAQASHIDI DI MA’HAD AL-QUR’AN UNIVERSITAS PTIQ JAKARTA - Darwis Hude; Made Saihu; Irhamil Muthoharoh; Otong Surasman; Mohammad Alfin Ni’am; Nurbaiti Nurbaiti (MPP: Lembaga Penelitian Dan Studi Kebijakan, 2025)
Childfree is a life decision or choice not to have biological children. The term Childfree only appeared at the end of the 20th century, but the phenomenon of childfree has only been discussed in Indonesia, and has caused many pros and cons among the public. People who decide to be childfree give reasons that the human population is too large and motherhood is not an obligation, but many people are against childfree for various reasons such as giving reasons by carrying the name of religion, with the argument that the prophet is proud of people who have many offspring. Because of this, the author wants to examine the child-free phenomenon using a tematik method with maqoshidi interpretation approach to find out the answers from the Qur'an. There are several verses from the Qur'an that allude to the childfree phenomenon, such as Surah an-Nahl 72 which explains that the purpose of marriage is to have children, and in Surah At-Taghobun verses 14-15 which explains that it can be a trial. Through the maqashidi interpretation approach, the authors found the initial hypothesis, namely that sometimes the pro childfree attitude contains benefits from the maqashid syariah point of view, and sometimes the contra attitude towards childfree can also be justified from the maqashid syariah point of view